Dampak Keterlibatan Pesantren dalam Politik: Studi Kasus Pesantren di Yogyakarta - Ernas, Saidin; Siregar, Ferry Muhammadsyah (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
Nowadays, many Islamic boarding schools (pesantren)start to involve in practical politics, turn out from their functionas Islamic education institutions. In fact, there are socio andpolitical impacts must be considered logically. This article basedon the research result in an Islamic boarding school in Yogyakarta.Using relevant theoretical frame, observation method, and depthinterview, this article tries to describe findings of politicalinvolvement in politics. Though this kind of practice giveeconomics material income, in the same time, decrease Islamicboarding schools legitimacy and impacts to community resistancetoward Islamic boarding school point of view.